'Chimwemwe Mu'bereki' (Joyful Motherhood): Closing the Gap in Unmet Need for Home Based Nurse Midwifery Care in High Risk Infants and Postpartum Women in Malawi. (27th October 2020) - Nosek, Marcianna; Chiwaula, Joanne
Abstract : Introduction: Although decreasing, maternal and infant mortality remain high in Malawi with and estimated 359 per 100, 000 live births for maternal mortality ratios, and 22.4 per 1000 live births for infant mortality. Joyful Motherhood (JM), or Chimwemwe mu'bereki, is a Malawian nonprofit organization, founded by a US midwife in 2008, which provides home‐based care to high‐risk, critically ill postpartum women and infants in rural villages of Lilongwe, Malawi. JM employs 3 nurse‐midwives who perform all community visits. Women served include, but are not limited to, those who experienced postpartum complications such as severe anemia, sepsis, eclampsia, or ruptured uterus, and complications related to HIV/AIDs. Infant clients include premature, low birth weight, multiples, and orphans who lost their mother in childbirth. All are enrolled for up to 2 years. The purpose of this mixed‐methods descriptive study was to evaluate the home visit nurse‐midwife programs of JM. There were 2 aims: (1) analyze descriptive data regarding clients served and (2) gain an understanding of the value of JM's services through the perspective of women and caregivers served. Research questions include: How many infants and women have been served since program inception? What are the infant and maternal mortality rates of JM's clients? How has JM's services benefitted clients served? Methods: Number of enrolled clients, annual visits made, and deaths were tracked by nurse‐midwives providing care and transferred to Microsoft Excel on a monthly basis by the program manager. Cumulative numbers and rates were calculated. Qualitative data were collected via one‐on‐one interviews and focus groups using a Chichewa interpreter and were digitally audiorecorded and transcribed. Results: From inception of program to July 2019, a total of 490 women and 1300 infants were served. Between October 2013 and July 2020, the infant mortality rate was 4.5% (46/1014) and maternal mortality rate was 1.4% (6/425). Twelve interviews and 2 focus groups were conducted to assess program effectiveness. Narratives revealed overwhelming gratitude for services provided. Participants expressed desperation when seeking care for family members unsuccessfully before being enrolled in JM. Many shared the infant visits were key in well‐being and survival of their child into early childhood. Themes include: tough times; very grateful for these gifts; encouraging us to care; and advise others. Discussion: JM's success for over 10 years demonstrates it is a viable model for unmet home care for high‐risk infants and postpartum women in Malawi. Financial challenges prevent scaling up of services and expansion of clientele. Efforts to improve data collection are ongoing including future plans to launch a new mobile electronic record app to use on smart phones.